2018
DOI: 10.3390/molecules23030647
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(η6,η1-arene-CH2-NHC) Catalysts for Direct Arylation of 2-Phenylpyridine with (Hetero)Aryl Chlorides in Water

Abstract: A series of new benzimidazolium halides were synthesized in good yields as unsymmetrical N-heterocyclic carbene (NHC) precursors containing the N–CH2–arene group. The benzimidazolium halides were readily converted into ruthenium(II)–NHC complexes with the general formula [RuCl2(η6,η1–arene–CH2–NHC)]. The structures of all new compounds were characterized by 1H NMR (Nuclear Magnetic Resonance), 13C NMR, FT-IR (Fourier Transform Infrared) spectroscopy and elemental analysis techniques. The single crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 56 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…278 More recently, O ̈zdemir and co-workers reported the monoselective C(sp 2 )−H arylation of 2-arylpyridines with aryl chlorides using benzimidazolylidene [Ru(NHC)Cl 2 ] complexes 218−221 under aqueous conditions (Scheme 142). 279 In 2010, Peris and co-workers reported [Ru(IBu)(pcym)Cl 2 ] 222 as a catalyst for the direct C(sp 2 )−H arylation of 2-arylpyridines with aryl bromides and aryl chlorides (Scheme 143). 280 This catalyst together with its N-Me and N-nOct analogues showed high activity for the diarylation of 2phenylpyridine and N-phenylpyrazole.…”
Section: Ruthenium−nhc Complexesmentioning
confidence: 99%
“…278 More recently, O ̈zdemir and co-workers reported the monoselective C(sp 2 )−H arylation of 2-arylpyridines with aryl chlorides using benzimidazolylidene [Ru(NHC)Cl 2 ] complexes 218−221 under aqueous conditions (Scheme 142). 279 In 2010, Peris and co-workers reported [Ru(IBu)(pcym)Cl 2 ] 222 as a catalyst for the direct C(sp 2 )−H arylation of 2-arylpyridines with aryl bromides and aryl chlorides (Scheme 143). 280 This catalyst together with its N-Me and N-nOct analogues showed high activity for the diarylation of 2phenylpyridine and N-phenylpyrazole.…”
Section: Ruthenium−nhc Complexesmentioning
confidence: 99%
“…133 Starting from these interesting results, Dixneuf and co-workers described the use of a chelate Ru(II) complex, able to catalyze the direct C-H bond ortho-arylation of both 1-phenylpyrazoles and 2-phenylpyridines with aryl bromides and chlorides in water, 134 and more recently also the application of a family of ruthenium(II)-NHC catalysts in the direct C-H bond ortho-arylation of 2-phenylpyridines with (hetero)aryl chlorides. 135 The ortho-arylation of 2-phenylpyridines with (hetero)aryl chlorides in water was also studied by Singh and co-workers, using a series of ad hoc synthesized troponate/aminotroponate Ru(II)-arene complexes as the catalyst, 136 and by Gimeno et al, who instead used commercially available RuCl 3 •nH 2 O in the presence of zinc powder. 137 It is worth emphasizing that in almost all of these studies the use of water as the reaction medium was mainly to allow the solubility of ruthenium catalysts, rather than for a real need to develop highly sustainable protocols.…”
Section: Direct C-h Bond Arylation Of (Hetero)arenes In Watermentioning
confidence: 99%
“…Initially, the metal–NHC complexes were used extensively as a catalyst in organic transformations such as C–C, C–heteroatom cross-couplings, and C–H functionalization. 53–64 In recent years, due to their strong σ-donors and easily tunable steric properties, low-toxic N-heterocyclic carbenes (NHCs) have been considered as effective ligands, which have the potential to overcome the shortcomings of phosphine-based catalytic instability and lead to achieve excellent catalytic performance. 55–66 Doucet et al for the first time, benzimidazolyl (NHCs)–Pd precatalysts have been shown to efficiently produce arylated thiophenes with a palladium loading of 1 mol% at 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…53–64 In recent years, due to their strong σ-donors and easily tunable steric properties, low-toxic N-heterocyclic carbenes (NHCs) have been considered as effective ligands, which have the potential to overcome the shortcomings of phosphine-based catalytic instability and lead to achieve excellent catalytic performance. 55–66 Doucet et al for the first time, benzimidazolyl (NHCs)–Pd precatalysts have been shown to efficiently produce arylated thiophenes with a palladium loading of 1 mol% at 150 °C. 67 In pyridine-enhanced precatalyst preparation stabilization and initiation (PEPPSI)-type palladium–NHC complexes, the methylene or phenylene linker of the NHC ligand allows additional degrees of rotation, which can guide the carbene ligand away from the metal center and avoid overloading.…”
Section: Introductionmentioning
confidence: 99%